Boosting Housing Markets: Amplifying Reserve Requirements for Greater Economic Growth, Insights from China and Indonesia - Rachmad, Sri Hartini; Hajriani, Meilisa; Basorudin, Muhammad; Fajar, Muhammad; Iriana, Nona; Dillena, Kennith G.C.; Wibisono, Okki Navarone (Jurnal Sains Matematika dan Statistika, 2024)
Enhancing the inclusivity, safety, resilience, and sustainability of urban areas, as outlined in Goal 11 of the Sustainable Development Goals (SDGs) to be accomplished by 2030, entails ensuring universal access to adequate, secure, and affordable housing along with essential services, and the enhancement of informal settlements. Consequently, numerous megacities worldwide grapple with burgeoning populations, precipitating a surge in housing costs, particularly exacerbated by volatile financial environments. The post-2013 financial recuperation in the United States precipitated a capital exodus towards Emerging economies, precipitating currency depreciation and imported inflation due to heavy reliance on foreign reserves. In response, the Indonesian central bank augmented reserve requirements to curtail money supply, while its Chinese counterpart reduced such requisites to stimulate economic expansion. This inquiry endeavors to discern the short-term impact of heightened reserve requirements on consumer, investment, and working capital credit pertinent to housing consumption, and in the long run, examines their ramifications on total output within the current account. Employing the Vector Error Correction Model (VECM), this study scrutinizes the central bank's credit policies' influence on overall output over both temporal horizons. Augmenting reserve requirements, integral to banks' balance sheets, impinges on liquidity and credit provisioning capacities, affecting not only consumer and housing credit but also investment and working capital credit, crucial financing conduits bolstering real sector activity and economic growth.